STUDI LIVING QUR’AN TERHADAP AMALAN IBU HAMIL DI KECAMATAN BERUNTUNG BARU KABUPATEN BANJAR - Isnawati Isnawati (Faculty of Ushuluddin and Humanities, 2015)
Along with the times, study the Koran and Hadith experiencing developments study area, from the study of texts to the socio-cultural studies, which is then referred to as “living Koran” and “living tradition”. In addition, living study the Koran that not only the existence of textual, but a social phenomenon that was born linked to the presence of the Koran in a specific geographic region and specific future anyway. However, the phenomenon appears not always directly proportional to what is supposed to be practiced and in amalkan. Seeing this phenomenon the author tries to do more research about reading (practice) of the Koran in public District of Lucky New Banjar Regency, the authors wanted to uncover the sura and verse what is used as a bidder, healer or medicine that mamampu cure physically and mental reserved for pregnant women. Any problems with the formulation of sura and verse of the Koran that used pregnant women, and then what are the factors that affect pregnant women mengamlkan suras and verses of the Koran in the District of New Lucky Banjar district.